THE PROBLEM OF SELF-AWARENESS IN PRESCHOOL PREPARATION GROUPS THEORETICALLY STUDIED (American Journal of Interdisciplinary Research and Development, 2022)
The article presents the opinions of foreign scientists on the role and importance of self-awareness of preschool children, that is, the concept of self.